Analisis Komitmen Organisasi Dengan Komitmen Profesional Di Lingkungan Bisnis Pangandaran - Nurul Mardhiah Sitio; Fadia Haaya (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2024)
The purpose of this study is to investigate how business ethics and work ethics affect organizational and professional commitment, with the professional commitment variable serving as an intermediary variable. The primary data for this study were gathered by filling out and submitting a questionnaire to the researcher on behalf of external auditors. The study's findings demonstrate that the external auditor performs his or her duties and serves as an external auditor more effectively the more he or she understands the accepted practice or rule of the workplace, whether it be business ethics, Islamic work ethics, or professional ethics. Additionally, it affects his organizational and professional commitments as an external auditor.